Labioplasty barsky technique in patients with complete bilateral cleft lip: Labioplasti secara teknik Barsky pada pasien celah-bibir bilateral - Raside, Hadira (Makassar Dental Journal, 2024)
Bilateral cleft lip is occured on both sides of the premaxilla either complete or incomplete so that in this situation there is no nor-mal side for comparison. Cleft lip and palate deformities are generally congenital abnormalities that require comprehensive ma-nagement. Barsky's technique is rarely used, but it is important to know the results in cases of BCC komplit. In this case review, a 16-month-old boy with a diagnosis of bilateral complete labiognatopalatoschizis underwent labioplasty with the Barsky tech-nique on his CL. Labioplasty was performed under general anaesthesia at the Unhas Teaching Dental Hospital. The Barsky tech-nique is a development of the Veau II technique, indicated in cases of CL with protrusive premaxilla and short prolabiun. It was concluded that CL can be treated with Barsky technique labioplasty.